The Effect of Iodine-125 Radioactive Particle Stent with Doxorubicin-loaded Nano-tetrahedrons Combined with Transarterial Chemoembolization on Survival and Prognosis of Patients with Cholangiocarcinoma: I-125 Radioactive Particle Stent on Cholangiocarcinoma - Wang, Gaobo; Ye, Guowei; Chen, Xugao; Ji, Zhong; Wu, Lingtong; Liu, Biao (Cellular and Molecular Biology, 2022)
This study was to analyze the application of doxorubicin-loaded DNA nano-tetrahedral Iodine-125 (I-125) radioactive particle stent (doxorubicin-loaded 125I stent) combined with transarterial chemoembolization (TACE) in improving the prognosis of patients with cholangiocarcinoma (CC). The doxorubicin-loaded DNA nano-tetrahedrons were constructed, the preparation plan was optimized, and the toxicity test was performed. The prepared doxorubicin-loaded DNA nano-tetrahedrons were applied to 85 cases in the K1 group (doxorubicin-loaded 125I + TACE), 85 cases in the K2 group (doxorubicin-loaded 125I), and 85 cases in K3 group (TACE). It was found that the optimal initial concentration of doxorubicin for the preparation of DNA-loaded nano-tetrahedrons was 200 mmol, and the optimal reaction time was 7 hours. The serum total bilirubin (TBIL) level in the K1 group at 30 days after operation was lower than that in the K2 and K3 groups at 7, 14 and 21 days. (P< 0.05). The alkaline phosphatase (ALP) level in the K1 group was lower in contrast to that in the other two groups at 7, 14, and 21 days after surgery (P< 0.05); and the five-year survival rate of patients in the K1 group was greater in contrast to the rate in K2 and K3 groups (P< 0.05). In short, the implantation of a doxorubicin-loaded 125I stent combined with TACE could effectively improve the five-year survival rate of patients with CC and improve the prognosis effect of the patients.